Enhancing Financial Accountability in NGOs through Effective Accounting Systems and Transparency: A Case Study from Gorkha, Nepal - Kandel , Madan; Joshi, Ramesh Datt; Pokhrel, Madan (NPRC Journal of Multidisciplinary Research, 2025)
This study examines the relationship between accounting systems, transparency, and financial accountability within non-governmental organizations (NGOs) in Gorkha district, Gandaki Province, Nepal. Using a quantitative approach and cross-sectional design, data were collected from 260 valid responses among board members, management committee members, and other stakeholders. The study employed statistical tools, including SPSS (version 23), to analyze correlations, factor analysis, and regression, establishing the association between accounting systems and financial accountability. Findings reveal a significant positive relationship between accounting systems and financial accountability, with transparency identified as a critical moderating variable. Accounting systems enhance accountability by ensuring proper record-keeping, compliance, and monitoring, while transparency amplifies these effects by fostering clarity and trust in financial processes. The regression analysis demonstrates that 56.4% of the variance in financial accountability is explained by accounting systems, transparency, and their interaction. These findings align with previous studies emphasizing the importance of structured accounting practices and adherence to Nepalese Accounting Standards (NAS). The study concludes that implementing robust accounting systems and promoting transparency are essential for improving financial accountability in Nepalese NGOs. Future research could explore other mediating factors and extend the scope to additional regions in Nepal to generalize findings.